Community-based support for children who are next-of-kin for a parent experiencing illness or disability - a scoping review - Anne Kjersti Myhrene Steffenak; Agneta Anderzén-Carlsson; Elin Opheim; Tuva Sandsdalen (BMC, 2021)
Abstract Introduction Children who are next-of-kin, for a parent who experience illness or disability, need support. In Norway, guidelines, routines and structured approaches in the community health services are lacking regarding involving children in the care of a parent and for services when supporting children as next-of-kin. Additionally, no existing international review has focused on support from community health and social services for children who are next-of-kin to a parent regardless of the specific illness or disability. Aims This scoping review examined the current knowledge regarding the types of community health and social services support to children 0 to 17 years old living with a parent experiencing illness or disability. The review also identified children's support preferences and needs. Methods The scoping review involved five stages; identifying research question; identifying relevant articles; selecting articles; charting the data and finally, collating, summarizing and reporting the results. Results Articles which included community health and social services interventions and children's preferences or needs for support were included. The foci of interventions included preventive education, peer support, psychosocial support, and interventions focusing on family communication and recovery planning. Articles focusing on children's preferences or need for support described their wish to be recognized as a next-of-kin, having someone to talk to and professional and peer support. Conclusion The review highlighted the importance of children receiving support according to their preferences. It is important to elicit children's voices, to ensure community health and social services are developed for and tailored to this population.